Postmastectomy radiation therapy after neoadjuvant chemotherapy: review and interpretation of available data - Amar U. Kishan; Susan A. McCloskey (Therapeutic Advances in Medical Oncology, 2016)
Postmastectomy radiotherapy (PMRT) has been shown to decrease locoregional recurrence and improve overall survival in patients with tumors greater than 5 cm or positive nodes. Because neoadjuvant chemotherapy (NAC) can cause significant downstaging, the indications for PMRT in the setting of NAC remain controversial and thus careful consideration of clinical stage at presentation, pathologic response to NAC, and other clinical characteristics, such as grade and biomarker status is required. The current review synthesizes both prospective and retrospective data to provide evidence for recommending PMRT after NAC for patients presenting with cT3–4 disease, cN2–3 disease, and residual nodal disease, as well as rationale for omitting PMRT in patients with cT1-2N0-1 disease who achieve a pathologic complete response. Other scenarios, including nodal complete response in the presence of other risk factors, are also explored. The topics of pre-NAC clinical staging and pathologic axillary nodal staging are reviewed, and radiation portal design is briefly discussed.